Commentary: Connecting With Children—Something That Cannot Be Taught (LEARNing Landscapes, 2013)
Tim Peters always knew he wanted to be a teacher but it was his experience as a ski instructor and the special connection he had with his students that confirmed his choice. In this interview, Mr. Peters explains that a key component of early childhood curriculum is to provide balance between structure and novelty and among school, extracurricular activities, and play. While the mandated curriculum has to be addressed, he advocates setting aside time for projects to create engagement both for the children and the teachers. He also expresses his views on differentiated learning and the importance of collaboration. Lastly, he believes that hiring teachers who are able to connect with students is key to creating an optimal learning environment.
Keywords: teacher; interview; connection; early childhood; curriculum; extracurricular activities; play; learning environment